Pengaruh Religiusitas, Persepsi Atribut Produk Dan Persepsi Nilai Terhadap Loyalitas Nasabah Pada Bank Syariah Indonesia Kantor Cabang Pembantu Palembang - Ingek Kustrian; Zuul Fitriani Umari; M. Iqbal (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Banks are the most important financial institutions and play a vital role in everyone's life. The problem in this study is that the majority of Indonesia's population is Muslim. This large Muslim population in Indonesia is problematic because the large number of Muslims in Indonesia does not make Islamic banks a market winner. This study aims to determine the influence of religiosity, product attribute perceptions, and value perceptions on customer loyalty at Bank Syariah Indonesia, Palembang Branch Office. This study used a questionnaire as the research instrument. The method used in this study was quantitative. The results showed a positive and significant influence between religiosity and customer loyalty at Bank Syariah Indonesia's Palembang Branch Office. There was a positive and significant influence between product attribute perceptions and customer loyalty at Bank Syariah Indonesia's Palembang Branch Office. There was a positive and significant influence between value perceptions and customer loyalty at Bank Syariah Indonesia's Palembang Branch Office. There was a positive and significant influence between religiosity, product attribute perceptions, and value perceptions simultaneously on customer loyalty at Bank Syariah Indonesia's Palembang Branch Office.